Ginsenosides as anticancer agents: in vitro and in vivo activities, structure-activity relationships, and molecular mechanisms of action - Nag, Subhasree A.; Qin, Jiangjiang; Wang, Wei; Wang, Ming-Hai; Wang, Hui; Zhang, Ruiwen (Frontiers in Pharmacology, 2012)
Conventional chemotherapeutic agents are often toxic not only to tumor cells but also to normal cells, limiting their therapeutic use in the clinic. Novel natural product anticancer compounds present an attractive alternative to synthetic compounds, based on their favorable safety and efficacy profiles. Several pre-clinical and clinical studies have demonstrated the anticancer potential of Panax ginseng, a widely used traditional Chinese medicine. The anti-tumor efficacy of ginseng is attributed mainly to the presence of saponins, known as ginsenosides. In this review, we focus on how ginsenosides exert their anticancer effects by modulation of diverse signaling pathways, including regulation of cell proliferation mediators (CDKs and cyclins), growth factors (c-myc, EGFR, and VEGF), tumor suppressors (p53 and p21), oncogenes (MDM2), cell death mediators (Bcl-2, Bcl-xL, XIAP, caspases, and death receptors), inflammatory response molecules (NF-κB and COX2), and protein kinases (JNK, Akt, and AMPK). We also discuss the structure-activity relationship (SAR) of various ginsenosides and their potential in the treatment of various human cancers. In summary, recent advances in the discovery and evaluation of ginsenosides as cancer therapeutic agents support further preclinical and clinical development of these agents for the treatment of primary and metastatic tumors.